Re-visiting the status of North-West Akokoid in relation to Yoruba (2014)
The North-West Akokoid speech forms are spoken by over 250,000 people in Akoko North-West Local Government of Ondo State, Nigeria. The origin of these people, as well as their speech forms is shrouded in mysteries. Majority of them refer to themselves as Yoruba and regard their speech forms as dialects of Yoruba. To compound this problem, some scholars in the intellectual circle appear to have agreed to this claim without any attempt to use established linguistic principle to confirm the claim. This paper presents systematic proofs to assert that these speech forms though, distantly related to Yoruba, are not its dialects. The Ibadan 400 wordlist was used to elicit data from 34 informants across the nine communities where these speech forms are spoken. In analysing our data, Pike’s discovery procedure in phonological analysis and Swadesh’s principles of lexicostatistics were employed. Of the 200 lexical items extracted for the lexicostatistics analysis, 60 items which constitute 30% are cognate with Yoruba. This establishes Akokoid and Yoruba as members of a macro-family called Defoid, and not as dialects of the same language